Highly Cooperative Photoswitching in Dihydropyrene Dimers. Issue 43 (26th August 2020) - Liesfeld, Pauline; Garmshausen, Yves; Budzak, Simon; Becker, Jonas; Dallmann, André; Jacquemin, Denis; Hecht, Stefan
Abstract: We present a strategy to achieve highly cooperative photoswitching, where the initial switching event greatly facilitates subsequent switching of the neighboring unit. By linking donor/acceptor substituted dihydropyrenes via suitable π‐conjugated bridges, the quantum yield of the second photochemical ring‐opening process could be enhanced by more than two orders of magnitude as compared to the first ring‐opening. As a result, the intermediate mixed switching state is not detected during photoisomerization although it is formed during the thermal back reaction. Comparing the switching behavior of various dimers, both experimentally and computationally, helped to unravel the crucial role of the bridging moiety connecting both photochromic units. The presented dihydropyrene dimer serves as model system for longer cooperative switching chains, which, in principle, should enable efficient and directional transfer of information along a molecularly defined path. Moreover, our concept allows to enhance the photosensitivity in oligomeric and polymeric systems and materials thereof. Abstract : Enhancing photoswitching efficiency: In the donor–acceptor substituted dihydropyrene dimer the quantum yield for the second ring‐opening is enhanced by more than two orders of magnitude compared to the first ring‐opening. Responsible is a cooperative switching effect which has been rationalized by theoretical calculations and is a general phenomenon for dihydropyrene dimers connected through suitable bridges in the 2, 7‐positions.